Which variables may affect underwater glide performance after a swimming start? - Hermosilla, F.; Yustres, I.; Psycharakis, S.; Santos del Cerro, J.; González-Mohíno, F.; González-Rave, J. M. (European Journal of Sport Science, 2022)
The underwater phase is perhaps the most important phase of the swimming start. To improve performance during the underwater phase, it is necessary to improve our understanding of the key variables affecting this phase. The main aim of this study was to identify key kinematic variables that are associated with the performance of an underwater glide of a swimming start, when performed at streamlined position without underwater undulatory swimming. Sixteen experienced swimmers performed 48 track starts and 20 kinematic variables were analysed. A multiple linear regression analysis was carried out to explore the relationship between glide performance (defined as glide distance) and the variables that may affect glide performance. Four variables in the regression model were identified as good predictors of glide distance: flight distance; average velocity between 5m and 10m; and maximum depth of the hip. The results of the present study help improve our understanding of underwater glide optimisation and could potentially facilitate improvement of overall start performance.